QM/MM study of N501 involved intermolecular interaction between SARS-CoV-2 receptor binding domain and antibody of human origin. (February 2023) - Liu, Yuemin; Sulaiman, Hana F.; Johnson, Bruce R.; Ma, Rulong; Gao, Yunxiang; Fernando, Harshica; Amarasekara, Ananda; Ashley-Oyewole, Andrea; Fan, Huajun; Ingram, Heaven N.; Briggs, James M.
Abstract: Intermolecular interaction between key residue N501 of the epitope on SARS-CoV-2 RBD and screening antibody B38 was studied using the QM/MM and QM approach. The QM/MM optimized geometry shows that angle X-H—Y is 165° for O-H—O between mAb light chain S30 and RBD N501. High level MP2 calculations indicated the interaction between RBD N501 and S30 of B38 Fab light chain provide a relatively strong attractive force of − 3.32 kcal/mol, whereas the hydrogen bond between RBD Q498 and S30 was quantified as 0.10 kcal/mol. The decrease in ESP partial charge on hydrogen atom of hydroxyl group on S30 drops from 0.38 a.u. to 0.31 a.u., exhibiting the sharing of 0.07 a.u. from the lone pair electron oxygen of N501 due to hydrogen bond formation. The NBO occupancy of hydrogen atom also decreases from 25.79 % to 22.93 % in the hydroxyl H-O NBO bond of S30. However, the minor change of NBO hybridization of hydroxyl oxygen of S30 from sp3.00 to sp3.05 implies the rigidity of hydrogen bond tetrahedral geometry in the relative dynamic protein complex. The O-H—O angle is 165° which is close but not exactly linear. The structural requirement for sp3 hybridization of oxygen for hydroxyl group on S30 and dimension of protein likely prevent O-H—O from adopting linear geometry. The hydrogen bond strengths were also calculated using a variety of DFT methods, and the result of − 3.33 kcal/mol from the M06L method is the closest to that of the MP2 calculation. Results of this work may aid in the COVID-19 vaccine and drug screening. Graphical Abstract: ga1 Highlights: QM/MM optimized hydrogen bond geometry between mAb light chain S30 and RBD N501. High level MP2 calculations of the interaction between RBD N501 and S30 of B38 Fab light chain. High level MP2 examination of ESP partial charge transfer of lone pair electron oxygen of N501, variations in orbital occupancy, and NBO hybridization of hydroxyl oxygen of S30 due to hydrogen bond formation. QM/MM simulation and MP2 QM verification of that hydrogen bond geometry being close but not exactly linear. Comparison of calculated hydrogen bond strengths using a variety of DFT methods with that of the MP2 calculation.